Yield on reinterpretation of genetic variants in pediatric cardiomyopathy - Suzuki, Takanori; Lesurf, Robert; Akilen, Rajadurai; Xu, Xiaoqiao; Batke, Eva Maria; Rao, Vinay J.; Jobling, Rebekah; Zahavich, Laura; Henden, Natasha; Ingles, Jodie; Torres, Edgardo Alania; Hirono, Keiichi; et al. (Journal of the American Heart Association, 2025)
Background - Variant interpretation can change over time as new knowledge emerges. Our aim was to determine the frequency and causes of variant reinterpretation on systematic reevaluation in pediatric patients with cardiomyopathy. - Methods - Overall, 227 unrelated pediatric patients with cardiomyopathy enrolled in the Heart Centre Biobank harbored a pathogenic/likely pathogenic (P/LP) variant or a variant of uncertain significance (VUS) on clinical genetic testing (2005-2022). Variant pathogenicity was reevaluated using the American College of Medical Genetics and Genomics guidelines. Additional extension cohorts (n=4547, cases) were analyzed to assess variant burden in cases versus controls (gnomAD 4.1.0). - Results - A total of 382 variants (110 P/LP, 272 VUS) in 227 patients were reevaluated. Forty‐nine variants in 49 patients (21.6%) changed classification. Twelve (10.9%) P/LP variants were downgraded to VUS in 14 patients. Leading criteria were high population allele frequency and variant not located in mutational hotspot or critical functional gene domain. Thirty‐seven (13.6%) VUS were upgraded to P/LP in 35 patients. Leading criteria were variant location in mutational hotspot for gene and deleteriousness on in silico prediction. Only 8 reclassified variants had been reported back by the clinical genetic testing laboratory at the time of the study. Ten of the 37 VUS upgraded to P/LP were significantly enriched in cardiomyopathy cases (n=4796) versus controls. - Conclusions - One in 5 patients with cardiomyopathy had a clinically relevant change in variant pathogenicity on systematic reevaluation that would require modifying family clinical screening and cascade genetic testing. These findings underscore the clinical importance of regular variant reinterpretation on follow‐up.
Gesehen am 17.02.2026